The law of making Transaksi false transactions to increase the sales of the perspective of the Mufti of the Federal Territory Fatwa number 590 (Carousell Malaysia Case Study Malaysia) - Abdul Rabbani Bin Abdul Razak; Cahaya Permata (Warmadewa Press, 2024)
Carousell as one of the online buying and selling sites that attracts customers to make more transactions through the site. Carousell is one of the mobile classified’s applications or classified ad-based applications. Established in 2012, Carousell is one of the online shopping places headquartered in Singapore and has grown in 13 countries including Indonesia, including Singapore, Malaysia, Indonesia, Taiwan, Hong Kong and the United States. Although Carousell is applications that get welcome good in Malaysia, application This No escape from lack. The problems he faced is the seller who does transaction false with buy the goods alone, then give evaluation and comment Alone For get trust buyer. Study This done for know the legal status action This based on runway Sharia along with the conditions that limit it in accordance with the fatwa of the Mufti of the Federal Territory. Study This use approach case based on method writing data analysis for to describe related issues with action buy products sold alone, then upload review and comment as part from strategy marketing business in Islamic perspective. Material law in study This obtained with to browse primary sources and secondary from Federal Territory Fatwa No. 590 and related matters with issue study This Results study This show that action the seller who does fraud the is haram. Although action This aiming for get good rating use increase sales, business increase sale the must be in harmony with what is allowed by Sharia.